Daily Weather Data From Central and Eastern King George Island (West Antarctica) for 2018–2023 - Joanna Plenzler; Tomasz Budzik; Kornelia Anna Wójcik‐Długoborska; Robert Józef Bialik (Geoscience Data Journal)
ABSTRACT The dataset presented in the paper contains meteorological data from four automatic weather stations (AWS) located in the central and western parts of King George Island (near Arctowski Station and Cape Lions Rump). The dataset includes daily mean, maximum and minimum values of air temperature, relative air humidity, air pressure, wind speed and daily sum of solar radiation. The measurement period ran from 2018.01.01 to 2023.12.31, but it is shorter for two of the stations. Mean values were calculated from measurements taken every 10 min. Direct measurements were used to identify extreme values. The described dataset consists offour files, each for one AWS. It is available in the PANGEA online repository under a non‐restrictive CC BY 4.0 licence for anyone after registration. Despite a strong correlation between the daily mean values of the parameters measured at certain stations, some differences between them were also noticeable. These were due to their location at different altitudes, in a place open to the sea or in a shaded place. Generally, values of wind speed, air humidity, solar radiation and pressure are similar to Arctowski during 2013–2017. The only notable distinction is that the mean annual air temperature and the mean air temperature in the winter months were higher than during 1977–1999 and 2013–2017. The data presented can be used as background for other research projects on King George Island, as well as for analysis of the meteorological conditions themselves. They may also be useful for the evaluation of the management plans of the eight Antarctic Specially Protected Areas or Antarctic Specially Managed Area no. 1 that are located on King George Island.